Pan-cancer analysis and single-cell analysis identifies the CENPN as a biomarker for survival prognosis and immunotherapy - Nie Zhang; Zhuoying He; Xuejin Qin; Ke Han; Zhengchun Zhu; Fei Zhong (Discover Oncology)
Abstract Background Centromere protein N (CENPN), located on chromosome 16q23.2, encodes vital nucleosome-associated complexes that are essential for dynamic assembly processes. CENPN plays a pivotal role in regulating cell proliferation and cell cycle progression by influencing mitotic events. Despite its potential importance, the precise functional role and regulatory mechanisms of CENPN in diverse malignancies remain largely unexplored. This study aimed to elucidate the role of CENPN in human cancers and evaluate its prognostic significance. Methods Investigate the role of CENPN in various malignancies, we leveraged data from The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) databases. We employed a comprehensive suite of web platforms and software tools for data analysis, including R, Cytoscape, an integrated repository portal for tumor-immune system interactions (TISIDB), CBio Cancer Genomics Portal (cBioPortal), Search Tool for the Retrieval of Interaction Gene/Proteins (STRING), Gene Set Cancer Analysis (GSCALite), and a cancer single-cell state atlas (CancerSEA). Results The findings demonstrated that CENPN expression was elevated in the majority of cancer types and differentially expressed across molecular and immune subtypes. Functional enrichment analysis in multiple tumors also identified possible pathways of CENPN involvement in tumorigenesis. Its expression positively correlated with Th2 and Tcm cells in most cancers. It is also correlated with genetic markers of immunomodulators in various cancers. Conclusions Overall, CENPN expression is closely related to cancers and has the potential to act as a cancer biomarker.